miR-155 Regulates IL-10-Producing CD24hiCD27+ B Cells and Impairs Their Function in Patients with Crohn’s Disease - Zheng, Yingxia; Ge, Wensong; Ma, Yanhui; Xie, Guohua; Wang, Weiwei; Han, Li; Bian, Bingxian; Li, Li; Shen, Lisong (Frontiers in Immunology, 2017)
Regulatory interleukin-10 (IL-10)-producing B cells (B10 cells) play a critical role in preventing and curing autoimmune diseases in experimental mouse models. However, the precise cellular and molecular mechanisms of action of B10 cells in humans, especially in patients with Crohn’s disease (CD), remain to be determined. miR-155 regulates many physiological and pathological conditions, including inflammation such as that in CD. In this study, we aimed to explore the effect of miRNA-155 on IL-10 production by B cells in healthy controls (HCs) and CD patients. Interestingly, we found that CD24hiCD27+ B cells express high levels of miRNA-155 and IL-10, which are positively correlated. Additionally, CD24hiCD27+ B cells express higher levels of Toll-like receptor 9 than those found in other B cell subsets. Overexpression of miRNA-155 promotes IL-10 production, while inhibition of miRNA-155 decreases IL-10 production. We determined that miR-155 directly inhibits the expression of Jarid2, which reduces H3K27me3 binding to the IL10 promoter and increases IL-10 gene expression. In coculture systems, the CD24hiCD27+ B cells from HCs suppressed the secretion of TNFα and IFNγ by monocytes and T cells, respectively. However, the number and function of CD24hiCD27+ B cells from CD patients were decreased. Moreover, we found that miR-155 induces CD24hiCD27+ B cells to produce higher levels of TNFα instead of IL-10 in CD patients than in the controls and that the increased number of IL-10+TNFα+ B cells reduces the induction of Foxp3 expression and the inhibition of IFNγ production by CD4+CD25− T cells, as well as TNFα production by monocytes. Our study demonstrates the critical role of miRNA-155 in the regulation of IL-10 production by B cells and reveals the novel molecular mechanism underlying the functional impairment of B10 cells in CD patients. Our study has the potential to drive the development of B10 cell-based strategies to ameliorate disease progression in CD patients.